MEXICO, THE CONTINUOUS CONSTRUCTION OF AN ILL-BEING REGIME - Gallardo Gómez, L. Rigoberto (2013)
As a consequence of a decision of the countries elites, which they have sustained for decades, the construction of an authentic Mexican regime of well-being, based on the collective effort of its people, has not been realized. Instead, this historical dynamic, which in its contemporary form continues to dominate the county’s economic, politi-cal, social and environmental arenas, is being compounded by the compensatory and targeted social policies of the state. It is leading the country down a path of construc-ting a regime of ill-being for the majority of its population.